Analysis of HIV Integrase Resistance in Black Men Who Have Sex with Men in the United States - Chen, Iris (AIDS Res Hum Retroviruses, 2017)
Resistance to reverse transcriptase and protease inhibitors was frequently detected in HIV from black men who have sex with men (MSM) enrolled in the HIV prevention trials network (HPTN) 061 study. In this study, integrase strand transfer inhibitor (INSTI) resistance was analyzed in black MSM enrolled in HPTN 061 (134 infected at enrollment and 23 seroconverters) and a follow-up study, HPTN 073 (eight seroconverters). The ViroSeq HIV-1 Integrase Genotyping Kit (Abbott Molecular) was used for analysis. Major INSTI resistance mutations were not detected in any of the samples. HIV from 14 (8.4%) of the 165 men, including 4 (12.9%) of 31 seroconverters, had accessory or polymorphic INSTI-associated mutations. The most frequently detected mutation was E157Q. These findings are promising because INSTI-based regimens are now recommended for first-line antiretroviral treatment and because long-acting cabotegravir is being evaluated for pre-exposure prophylaxis.